A Comparative Analysis of Work Regulatory Focus on Cross-Generational Employees at PT. "X" - Deri Setyawan; Anindra Guspa (In Trend : International Journal of Trends in Global Psychological Science and Education, 2025)
The variability of individual characteristics in the workplace relates to how they achieve their goals at work. If the direction of work regulations is not in accordance with the desired goals, then the balance between personal life and work expected by employees will not be achieved. This study is a comparative quantitative research that aims to see the difference between three subjects with the same variable not to investigate causal relationships. This study uses Analysis of Variance (ANOVA) to identify whether there is a difference in the focus of labor regulations among Generation X, Y, and Z workers at PT. "X". The results show that Generation X has the lowest average in both dimensions as a comparison. There is a significant difference between Generation Y and Generation Z, with a p-value of .000 (p<0.001). This study revealed significant differences in the characteristics and work preferences between Generation X, Y, and Z in the Prevention Focus and Promotion Focus variables. Further analysis shows that Generation Y and Z, who value flexibility and are more open to technology, are in contrast to Generation X, who prioritize stability and structure.